Exploring the Quality Improvement in Small Scale Project Using Aspect-Oriented Design - Chishti, Sufia Nadeem; Singh, S. K. (International journal of recent technology and engineering, 2019)
Aspect-oriented software development (AOSD) seeks to renovate the software quality by use of alteration to the design in object-oriented based systems. Each system component has been divided into numbers of modules and arranges a design in a way that the module has not crosscut to each other. A module is a collection of block of codes, whose role is to restrict and conceal the design definition. This type of behavior is known as the Separation of Concerns (SoC). AOP helps programmers for separating crosscutting concerns. It can be helpful at better modularizing system, the problem with complex system is that the component require different, crosscutting descriptions at different levels and need maintenance too. In this paper, a study was conducted to analyses quality in aspect-oriented software design. This paper also explores varieties of existing metrics related to AOP also and will discuss in detail with comparison of OOPs using small scale projects that how the new programming paradigm design effects on quality of the software.